Assessment of Quality of Built Environment in the Urban Villages of Delhi - Bipasha Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Urban Villages are integrated part of the development in the cities. In the process of Urbanization, the villages of Delhi have been engulfed and as a result the rural villages are transformed to urban villages. The Urban Villages in Delhi are growing fast and haphazardly. This necessitates systematic understanding and a structure for measuring the quality of built environment specifically acceptable to Urban Villages. In the existing situation, there is no structure for measuring and assessing the built environment of these villages. This nonexistence of assessment structure has resulted to the unmanageable growth of these villages, which has triggered a sequence of environmental, social, and economic issues. This paper firstly analyses prevailing assessment methodologies, reviews the theories on Quality Assessment of built environment and proposes an Assessment Structure that is appropriate to this area and similar areas. The structure is specially made for urban villages to address its characteristic issues. The structure is built on a quality assessment model for urban villages that highlights the physical aspects; and considers the environmental and social conditions of urban villages into explanation. The assessment structure is tested in the two urban villages of Delhi as the development pace is very high in these villages and the infrastructure development is low in comparison. Finally, the factors liable to the degraded urban quality of the Urban Villages are validated which can help architects, planners and other professionals in ascertaining innovative and challenging development regions.